Fatigue reliability and service life prediction of aluminum naval ship details based on monitoring data. (January 2015) - Soliman, Mohamed; Barone, Giorgio; Frangopol, Dan M
The evolution of naval vessels toward high-speed crafts subjected to severe sea conditions has promoted an increasing interest in lightweight high-strength materials. Due to its strength and weight characteristics, aluminum has been proven especially suitable as construction material for hull structures as well as other vessel parts. However, fatigue in aluminum naval crafts needs to be effectively addressed for the proper life-cycle assessment. Structural health monitoring systems constitute effective tools for measuring the structural response and assessing the structural performance under actual operational conditions. In this article, an approach for using structural health monitoring information in the fatigue reliability analysis and service life prediction of aluminum naval vessels is presented. The accumulated fatigue damage and the fatigue reliability are quantified based on structural health monitoring data acquired under different operational conditions, specified by the ship speeds, sea states, and heading angles. Additionally, an approach for estimating the reliability-based fatigue life under a given operational profile is presented. Seakeeping trial data of an aluminum high-speed naval vessel are used to illustrate the proposed approach.